Overview of privacy preserving in social network - Rui-xin YAO; Hui LI; Jin CAO (网络与信息安全学报)
Social network has gradually become the main way in communication with the development of informa-tion technology and the issue of privacy preserving in social network has also obtained more and more attention due to the interactive information exposed in the open social networks.Firstly,an overview of the concept of social net-work and privacy was givem.Secondly,the current mainly two methods:anonymity mechanism and access control technique employed for privacy preservation in social networks were reviewed and discussed.Finally,the vulner-abilities and challenges of the current mechanism were analyzed and the potential research issues for the future re-search works were showed.